The Effect of Outflow Launching Radial Efficiency of Accretion Disk on the Shape of Emission-Line Profiles - Mohammad Hassan Naddaf (Universe)
This paper presents a preliminary investigation into the influence of radial behavior of disk outflow on the structure and dynamics of the broad line region (BLR) in active galactic nuclei (AGNs), with an emphasis on how the mass ejection rate contributes to shaping the broad emission-line profiles. Specifically, we analyze how varying the radial efficiency of mass loss from accretion disks, driven by radiative dust-based mechanisms, contributes to the distribution of material in the BLR. By exploring different radial scenarios of disk mass loss behavior, we uncover connections between outflow radial efficiency and emission line profiles, particularly for lowly ionized lines. Our findings reveal that while the observed shape of broad emission lines is partially influenced by the radial behavior of the disk outflow, it ultimately depends more critically on the physical conditions of the clouds and the specific approach adopted regarding the emissivity for their contribution to the line formation.